Breeding experiments and genome‐wide association analysis elucidate two genetically different forms of non‐syndromic congenital cleft lip and jaw in Vorderwald × Montbéliarde cattle. (24th July 2017) - Reinartz, S.; Distl, O.
Summary: Non‐syndromic congenital cleft lip and jaw (CLJ) is a condition reported in Vorderwald × Montbéliarde cattle. The objective of the present study was to perform a genome‐wide association study (GWAS) for 10 CLJ‐affected and 50 unaffected Vorderwald × Montbéliarde cattle using the bovine Illumina high density bead chip to identify loci for this condition. Phenotypic classification of CLJ was based on a detailed recording of orofacial structures using computed tomography. A breeding experiment among CLJ‐affected Vorderwald × Montbéliarde cattle and CLJ‐affected Vorderwald × Montbéliarde cattle with unaffected Holsteins confirmed recessive inheritance and different loci for bilateral or left‐sided versus right‐sided CLJ. The GWAS for the five cases with right‐sided CLJ gave a genome‐wide signal on bovine chromosome (BTA) 29 at 16 Mb. For the four left‐sided and one bilateral CLJ case, a genome‐wide significant association was identified on BTA4 at 32 Mb. Two different loci are very likely to be involved in CLJ in Vorderwald × Montbéliarde cattle because experimental matings among affected cows and bulls with different types of CLJ did not result in CLJ‐affected progeny, and in addition, two different loci were also found through GWAS and mapped on two different bovine chromosomes. Validation in 346 Vorderwald × Montbéliarde cattle for the highly associated SNPs on BTA4 and 29 gave ratios of 33/346 (0.095, BTA4) and 6/346 (0.017, BTA29) homozygous mutant genotypes. Further studies should elucidate the responsible mutations underlying the different types of CLJ in Vorderwald × Montbéliarde cattle.